Methods of eloquent analogy in the Noble Qur’an - an analytical rhetorical study: أساليب التشبيه البليغ في القرآن الكريم-دراسة بلاغية تحليلية - Barkati, Muhammad Kashif; Sadidi, Dr. Mumtaz Ahmad (Al-Aijaz Research Journal of Islamic Studies & Humanities, 2025)
The Arabic language has branches of its sciences such as grammar, morphology, and rhetoric. Rhetoric is divided into the many inquiries, and in general it was divided into three sections: the science of meanings, the statement, and the bade. One of the topics of science statement analogy. As for this, the Qur’an verses contain the beauty of rhetorical methods. The eloquent analogy in the Holy Qur’an is one of the rhetorical methods that enhance the strength of the Qur’anic message, as it contributes to making the meanings clearer and more convincing, and raises feelings of reflection and reflection in the reader or listener, and it is one of the rhetorical methods in which the Holy Qur’an uses accurate and powerful images to express meanings, in order to facilitate their understanding and delivery to the recipient effectively. In this type of analogy, something is compared to something else using a simile (such as "as" or "like"), but it is often so precise and detailed that it contributes to reinforcing the intended idea or meaning. The writer chooses the holy Quran, because it contains many methods of simile. With this research, he wanted to investigate the methods of simile and its purposes, because the methods of imitation have special purposes and goals to confirm the meaning contained in the verse, and their purposes differ between one verse and the other verse.